If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x = x + 2 + 10 Reorder the terms: 3x = 2 + 10 + x Combine like terms: 2 + 10 = 12 3x = 12 + x Solving 3x = 12 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 3x + -1x = 12 + x + -1x Combine like terms: 3x + -1x = 2x 2x = 12 + x + -1x Combine like terms: x + -1x = 0 2x = 12 + 0 2x = 12 Divide each side by '2'. x = 6 Simplifying x = 6
| 15+47.45x=49.95x | | 2g+10=7g | | 6x+4x+3+7=5x+3+4x | | 9.5z=-161.5 | | 3x+12=-5x-60 | | (9x-15)^(1/2)=(7x-5)^(1/2) | | -3y+-y= | | 9.5z=161.5 | | 88-117=-6(-4y)-13(2y)+y | | y=6(x-4)2-7 | | 11x-0=16 | | -4n+9n-6=-58 | | 7y/6-1/6 | | -6x*3/4 | | 3/10m=25 | | 0.5n+0.5n+n=180 | | (3*x)+(3*8)=42 | | 2x-(x-2)=11 | | 2b-3+4b= | | 2(x+4)=2(-8-x-2x) | | 44-7x=20+5x | | 2z+3=4x+5 | | 8x-5=5m+7 | | 2m-5(5m+4)=-89 | | 12g=12(0.6g-1)+11 | | 114+x=5x | | 6n-14=4n | | 5x+40-3=51 | | 15-11(3m-2)+4(8m-9)-10= | | 5x-2/3(3x-9) | | 7=91 | | -5x+6x-7=7x+5 |